International Monetary Fund Annual Report 1951. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1951)
This paper reviews key findings of the IMF's Annual Report for the fiscal year 1951. The report highlights that the year 1950 was the first postwar year in which progress toward general balance-of-payments equilibrium appeared to bring that objective within sight. Many countries outside the United States increased their U.S. dollar holdings and were able to make net purchases of gold from the United States. This favorable trend became particularly evident after the devaluations of September 1949.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet